Effects of remifentanil on awakening of propofol sedated patients submitted to upper gastrointestinal endoscopy: a randomized clinical trial - Uliana,Gustavo Nadal (2020)
Abstract Background and objectives: Sedation for endoscopic procedures aims to provide high quality sedation, lower risks, short recovery time, superior recovery quality and absence of side effects, seeking high patient level of satisfaction. The goal of the study was to assess administration of remifentanil combined with propofol regarding the effects of the drug association during sedation and recovery for patients submitted to upper gastrointestinal diagnostic endoscopy. Method: One hundred and five patients were assessed, randomly divided into three groups of 35 patients. The Control Group was sedated with propofol alone. Study Group 1 was sedated with a fixed dose of 0.2 µg.kg−1 remifentanil combined with propofol. Study Group 2 was sedated with 0.3 µg.kg−1 remifentanil combined with propofol. We assessed the quality of sedation, hemodynamic parameters, incidence of significant hypoxemia, time for spontaneous eye opening, post-anesthetic recovery time, quality of post-anesthetic recovery, presence of side effects and patient satisfaction. Results: Study Group 1 showed better quality of sedation. The groups in which remifentanil was administered combined with propofol showed shorter eye-opening time and shorter post-anesthetic recovery time compared to the control group. The three groups presented hemodynamic changes at some of the moments assessed. The incidence of significant hypoxemia, the quality of post-anesthetic recovery, the incidence of side effects and patient satisfaction were similar in the three groups. Conclusions: The combination of propofol with remifentanil at a dose of 0.2 µg.kg−1 was effective in improving the quality of sedation, and at doses of 0.2 µg.kg−1 and 0.3 µg.kg−1 reduced the time to spontaneous eye opening and post-anesthetic recovery in comparison to sedation with propofol administered alone.